University Environment in Student Assessments: Case of the Russian University of Transport - M. Yu. Bykov; V. Ya. Krasnikovskiy; N. Yu. Matveeva; E. V. Yaryna (Высшее образование в России, 2023)
The university environment includes various material and intangible aspects that are subjected now to active changes associated with both the development of information tech-nology and the new needs of young people. Therefore, the attitude of students to their university environment is an actual research topic. The Russian University of Transport (RUT (MIIT)) conducted the online survey of students, during which they were asked an open question regarding university problems and university development. The results showed that the problems associated with communication and mutual understanding, taking into account their opinions and interests, are of the greatest importance for modern students. The wishes of the students to the teaching staff were expressed, from which it is required both the ability to clearly explain the subject, and the presence of an individual and respectful approach to each student. We should not forget about the need of modern students in obtaining practice-oriented modern knowledge and skills, often associated with the need to rejuvenate teaching staff. Attention is paid to aspects related to improving the infrastructure of the university, the educational process. The problems related to the extracurricular scientific and educational life of the university, cultural and sports activities, environmental issues, schedule and mode of classes, work of educational departments are disclosed. The development of political education and patriotism in the university depends on small but effective events and the presence of an organizing groups. The novelty of the obtained data is due to the fact that the answers to an open question always differ from the opinions received in the course of polls with pre-proposed answers, and make it possible to identify hidden trends in public opinion. Respondents, in this case, express what worries them first of all, express the wishes that come to mind first, without prompts. The findings indicate the need to develop a strategy for improving the educational environment of the university, aimed at developing the possibilities of direct communication, increasing informal, understanding interactions.